Kemiskinan Sebagai Pemicu Perceraian dalam Perspektif Yuridis - Hanapi, Agustin; Abubakar, Azmi; Lubis, Asmualiadi (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
Every marriage requires harmornisan and also permanence, to realize that, harmony between spouses is very important. This harmony in marriage law is called kafaah. The benchmark is not only compatibility in morals, but also related to age, social status and education. Many divorce phenomena occur due to the unfulfillment of the income of wives and children. Further explored this is due to the poverty factor caused by many variables. This study was conducted to answer two questions, first whether poverty is a contributing factor to divorce. Second, what is the reason for the divorce that occurred in the Pidie community. This research is classified as field research with a qualitative approach. The methodology used is the study of phenomena in the maqāṣid review. The results of the study concluded that the peceraian factor is caused by many aspects, poverty is one of them. As for divorces that occur due to poverty dip.